Analisis Faktor yang Mempengaruhi Keputusan Pembelian pada Pusat Jajanan Kota Langsa - Rahmi Meutia; Ivan Aulia (Jurnal Manajemen dan Keuangan, 2019)
The aim of this study is to determine the effect of product quality, servicescape and service quality to buyer’s purchasing decision in Langsa Snack Center. This study has 96 sample respondents with multiple linear regression analysis is choosen. The proof of hypothesis uses the T test, F test, and analysis of the coefficient of determination. Multiple linear regression analysis result shows Y = 1,549 + 0,191X1 + 0,272X2 + 0,258X3 and coefficient of determination result (Adjusted R Square) shows 0,664 or 66,40%. It shows the variables of product quality, servicescape and service quality affect purchasing decisions at the Langsa City Snack Center by 66,40%, while the remaining 33,60% is influenced by other variables not examined in this study such as price and location. T test results obtained partially product quality, servicescape and service quality significantly influence purchasing decisions at the Langsa City Snack Center. F test results obtained simultaneously product quality, servicescape and service quality significantly influence purchasing decisions at the Langsa City Snack Center